Splenic Pregnancy: A Diagnostic Dilemma (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Pregnancy in spleen is an infrequent incidence. Hence its outcome is meant to be much more alarming when it ruptures than usual site tubal ectopic. A 29 years old woman presented at her 9 weeks of gestation with loose motion and repeated vomiting. She had a previous history of ectopic pregnancy. She confirmed her pregnancy by urinary strip test but no Ultrasonogram was done. She was received in a state of shock. Ultrasonography revealed abdominal collection and βHCG was raised. Laparotomy was done as a case of tubal ruptured ectopic. Surprisingly ectopic site was in the spleen and splenectomy was done. A number of case reports and literature review are discussed to explore how the splenic ectopic pregnancy present, how these cases are managed and what could be done to alleviate this misery.Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):113-116